Transformation Cultural Identity In The Global Era: A Study Of Globalization And Locality - Merung, Arteurt Yoseph; Larisu, Zulfiah; Bahriyah, Euis Nurul; Ulhaq, Muhammad Zia (PT. Anagata Sembagi Education, 2024)
Globalization brings significant changes to local cultural identities through the influence of media, technology, and migration. Global cultures often dominate local cultures, creating challenges for societies that previously had stable cultural identities. This transformation has an impact on the way people interpret their collective identity. Although many studies have addressed the impact of globalization on cultural identity, an in-depth understanding of this transformation process is still limited. This research aims to fill this gap by examining the interaction between global and local cultures and how they form new, more complex identities. Using a qualitative approach with case study methods in Yogyakarta, Bali, and Bandung, this study collects data through in-depth interviews, participatory observations, and document analysis. The results show that the transformation of cultural identity is different in each region. In Yogyakarta, local culture remains dominant despite the influence of modern art; in Bali, globalization is seen in tourism that combines local and global cultures; while in Bandung, global pop culture is accepted by the millennial generation without leaving local identity. This research reveals that cultural adaptation creates a dynamic identity, where people choose relevant global elements, enriching cultural expression without losing local values